2016
DOI: 10.1111/jfpp.12911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal and Alternate Thermal Processing on Bottle Gourd (L agenaria siceraria ) Juice

Abstract: Bottle gourd juice (BGJ), a rich source of nutrients can support the growth of microbes that cause spoilage. Processing methods used to reduce number of microbes have adverse affects on nutritional quality of BGJ. The purpose of this research work was to examine the microbial safety and quality changes during conventional and alternate thermal methods without addition of additives. Different physico-chemical, functional and microbial parameters were studied for conventional and alternate thermal treatments. BG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…The decrement in the amount of organic acids was higher in pasteurized juice sample as compared to microwave processing. The reduction of organic acid after pasteurization processing of bottle ground juice was also reported (Bhat, Saini, Kumar, & Sharma, ). On the other hand, Igual et al () reported that the concentration of citric, malic, and tartaric acids in grapefruit juice fall to 10%, 4%, and 20% after microwave processing as compared to fresh juice which was less effective than conventional pasteurization.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The decrement in the amount of organic acids was higher in pasteurized juice sample as compared to microwave processing. The reduction of organic acid after pasteurization processing of bottle ground juice was also reported (Bhat, Saini, Kumar, & Sharma, ). On the other hand, Igual et al () reported that the concentration of citric, malic, and tartaric acids in grapefruit juice fall to 10%, 4%, and 20% after microwave processing as compared to fresh juice which was less effective than conventional pasteurization.…”
Section: Resultssupporting
confidence: 52%
“…The decrement in the amount of organic acids was higher in pasteurized juice sample as compared to microwave processing. The reduction of organic acid after pasteurization processing of bottle ground juice was also reported (Bhat, Saini, Kumar, & Sharma, 2017). On the other hand, Igual et al…”
Section: Hplc Quantification Of Organic Acidsmentioning
confidence: 85%
“…With regard to the applications of OH in the juice industry, a broad range of studies focused on its suitability for replacing traditional heating processes, studying in turn its effects on the nutrients in processed juices (Traffano‐Schiffo and others ) (Table ). Bhat and others () confirmed this statement, suggesting that OH is a promising alternative to conventional thermal technologies with a maximum retention of functional components and the complete destruction of microorganisms in bottle gourd juice. Similarly, other studies reported: (1) the lack of the effect on the flavor of many juice blends during the refrigerated storage for 2 wk (Dima and others ); (2) the retention of the carotenoids in orange and grapefruit juices (Achir and others ); (3) a moderate loss of ascorbic acid in carrot/celery/beetroot juice blend (Profir and Vizireanu ); and (4) any effect on the overall quality of orange and pineapple juices (Tumpanuvatr and Jittanit ).…”
Section: Thermal Treatmentsmentioning
confidence: 78%
“…Ascorbic acid was estimated by following the standard method (Bhat et al, ). The ascorbic acid was calculated as:mg AA/100g of sample=titre×dye factor×volume made×100Wt of sample taken…”
Section: Methodsmentioning
confidence: 99%
“…Bottle gourd, which is widely consumed, has not been so far explored for the scientific aspects. Application of different processing techniques have recently been reported (Bhat, Saini, & Sharma, ; Bhat, Saini, Kumar, & Sharma, ; Bhat & Sharma, ). However, juice extraction is a critical phenomenon in case of vegetables like bottle gourd due to intensive enzymatic activity and phenolic content.…”
Section: Introductionmentioning
confidence: 99%